2004
DOI: 10.4097/kjae.2004.47.4.505
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Infrared Thermal Imaging in Herpes Zoster Patients

Abstract: Background: Herpetic disorders cause pain and skin lesion. So, asymmetric temperature of both sides of the involving dermatome has been reported in thermogram. This study examined the usefulness of infrared thermography for a predictor of post-herpetic neuralgia (PHN).Methods: Patients with acute herpes zoster who underwent nerve block were randomly selected. Biographic data, including age, gender and times of onset of the skin lesions, development of PHN, combined diseases were recorded. Infrared thermography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The thermal pattern of neuropathic pain is usually hyperthermia in the acute stage and hypothermia in the chronic stage (10); previous application of a thermogram to HZ patients confirmed the above‐mentioned thermal pattern (10–12). It is suggested that the antidromic vasodilation triggered by neurosecretion from hyperactive nociceptors in the acute stage of neuropathic pain causes hyperthermia; meanwhile, sympathetic overactivation‐driven vasoconstriction or denervation‐driven muscular hypoactivity in the chronic stage causes hypothermia in a thermogram (13, 14).…”
Section: Discussionmentioning
confidence: 99%
“…The thermal pattern of neuropathic pain is usually hyperthermia in the acute stage and hypothermia in the chronic stage (10); previous application of a thermogram to HZ patients confirmed the above‐mentioned thermal pattern (10–12). It is suggested that the antidromic vasodilation triggered by neurosecretion from hyperactive nociceptors in the acute stage of neuropathic pain causes hyperthermia; meanwhile, sympathetic overactivation‐driven vasoconstriction or denervation‐driven muscular hypoactivity in the chronic stage causes hypothermia in a thermogram (13, 14).…”
Section: Discussionmentioning
confidence: 99%
“…It shows that the size of the wound after 4 months, which leaves scar such as pigmentation, can be a strong prediction factor, rather than the total size of wounds. The bigger the size of scar and the severity of pain also can be the prediction factor [20]. The reason why we excluded diabetes and cancer as a prediction factor in this research was that much larger patients group than ours should be required to gain more accurate result.…”
Section: Discussionmentioning
confidence: 93%
“…Aleanakian et al reported no correlation between temperature change in the involved extremity and pain reduction. This could possibly have been because of the following reasons: First, one does not expect temperature changes to occur following sympathetic blockade in cases of AHZ, 5 and second, the SGB was performed at a relatively high level (C6 tubercle), whereas temperature monitoring was done in the upper limbs. 3 Further results of all the groups related to temperature change have been merged together by Aleanakian et al, which could be a cause of bias because the results when split show meaningful data that temperature fluctuations were significant in the CRPS group and not so significant in the NP group.…”
mentioning
confidence: 99%